Perception of Pre-Service Teachers Regarding Digital Competencies in Indonesia (Jurnal Pendidikan Fisika, 2023)
This article aims to evaluate the digital competencies of prospective teachers in Indonesia in the context of digital education. A survey method was used to collect data from students and alumni of the physics education program from 2017 to 2022. A total of 248 respondents participated in the study, consisting of 202 students and 46 alumni. The collected data were then analyzed quantitatively. The research findings indicate that the majority of respondents showed a positive response to their abilities in all assessed dimensions of digital competencies. Literacy in information and data, communication and collaboration, digital content creation, safety, and problem-solving received favorable ratings. However, there is potential to improve skills in digital content creation. Overall, the respondents demonstrated a good level of competence in the evaluated digital competency indicators. The data also revealed that students and alumni of the physics education program are accustomed to using technology in their academic activities. They utilize Learning Management Systems (LMS) to access course materials, submit assignments, and take exams. Additionally, they employ various applications and collaborate online in groups. The program also offers courses that support the use of technology in learning. In conclusion, the perception of pre-service teachers towards digital competence is positive due to the support provided by the study program in offering technology-integrated courses.